2014
DOI: 10.7314/apjcp.2014.15.4.1581
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and Cisplatin in First Line Treatment of Patients with Unknown Primary Cancer: A Multicenter Study of the Anatolian Society of Medical Oncology

Abstract: Background: The overall prognosis for cancers of unknown primary (CUP) is poor, median overall survival (OS) being 6-12 months. We evaluated our multicentric retrospective experience for CUP administered docetaxel and cisplatin combination therapy. Materials and Methods: A total of 29 patients that were pathologically confirmed subtypes of CUP were included in the study. The combination of docetaxel (75 mg/m 2 , day 1) and cisplatin (75 mg/m 2 , day 1) was performed as a first line regimen every 21 days. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(21 reference statements)
1
7
1
Order By: Relevance
“…The median time of overall survival ranged from 12 to 18 months, which was clearly shorter than the median survival typically observed in more common types of prostate cancer. 2,9,10 Consistent with these earlier reports, platinum-based chemotherapy, such as SOX or EP therapy, did not prevent disease progression in our case. Although chemoradiotherapy combined with hormonal therapy played a role in shrinking the tumor and controlling some symptoms caused by cancer progression, its efficacy was limited to temporary local control.…”
Section: Discussionsupporting
confidence: 92%
“…The median time of overall survival ranged from 12 to 18 months, which was clearly shorter than the median survival typically observed in more common types of prostate cancer. 2,9,10 Consistent with these earlier reports, platinum-based chemotherapy, such as SOX or EP therapy, did not prevent disease progression in our case. Although chemoradiotherapy combined with hormonal therapy played a role in shrinking the tumor and controlling some symptoms caused by cancer progression, its efficacy was limited to temporary local control.…”
Section: Discussionsupporting
confidence: 92%
“…However, some studies have estimated a 5-year survival which is much higher than this study (Durante et al, 2009;Demirci et al, 2014).…”
Section: Discussioncontrasting
confidence: 63%
“…Sorbye and colleagues results were similar in treatment of neuroendocrine tumors (Sorbye et al, 2013). There is another study using combination of docetaxol and cisplatin in the treatment of metastatic neuroendocrine tumors of unknown origin regardless of differentiation of tumors (Demirci et al, 2014). However, only 3.4% of tumors were reported as well differentiated and toxicity was high.…”
Section: Discussionmentioning
confidence: 82%
“…Platinum-based chemotherapy in combination with paclitaxel, docetaxel, gemcitabine, and irinotecan has been reported to have objective response rates ranging from 18% to 55%. 41 45 Although there is no standard treatment for CUP, proper management can still lead to long-term survivorship. Kaizu et al demonstrated that definitive chemoradiation with platinum-based chemotherapy for cervical lymph node metastases from CUP was well tolerated, with a 5-year overall survival of 52%.…”
Section: Discussionmentioning
confidence: 99%